Unraveling the relationship between stress exposure and childhood anxiety: Considering accumulation, impact, and type in the first five years of life. - Viviane Valdes; Linda W Craighead; Charles A Nelson; Michelle Bosquet Enlow (PLoS ONE)
Exposure to stressful events is linked to anxiety symptoms in children, although research examining this association in the first five years of life is limited. We sought to examine the role of various aspects of family stressful experiences such as the total accumulation, impact, and type (measured longitudinally in the first five years of life) on child anxiety symptoms at age 5 years. A community sample of children and their parents (N = 399) enrolled in a longitudinal study of emotion processing were assessed when the children were infants and at ages 2 years, 3 years, and 5 years. Parents completed the Revised Life Events Questionnaire (all visits) to assess family exposures to stressful life events and the Child Behavior Checklist (5 years) to assess child emotional and behavioral symptoms. Analyses showed that total stressful events accumulated by 4 years were significantly associated with child anxiety symptoms at 5 years (r = 0.118, p = 0.045). Total stressful events accumulated at earlier time points (by 1 year, 2 years, and 3 years of age) were not significantly associated with child anxiety symptoms at 5 years. Events reported as being impactful by families appeared to be more sensitive than total events, with accumulated impactful events as early as 1 year being significantly associated with child anxiety symptoms at 5 years (r = 0.112, p = 0.042). When considering types of stressors, cumulative exposure from the prenatal period to 5 years to financial stressors (β = 0.12, p = .035) was most saliently and significantly associated with child anxiety symptoms at 5 years (after adjusting for other categories of stress such as health, interpersonal, and logistical stressors). Together, these findings suggest that stressful life events accumulated in early life, particularly those rated as impactful for the family and those related to finances, are associated with child anxiety symptoms at 5 years.